Impact of Health Education on Infectious Disease Knowledge in Indigenous Communities in Northwestern Malaysia - Barathan Muttiah; Wathiqah Wahid; Alfizah Hanafiah (Tropical Medicine and Infectious Disease)
Indigenous people possess unique health literacy issues and challenges with preventing infectious diseases. This research assessed the baseline knowledge and misinformation in the Semai indigenous subgroup in Perak state, Malaysia, and the impact of a culturally adapted health education intervention. A single-group pre-test/post-test design was used with 156 participants ranging from 7 to 69 years old, predominantly children. The survey addressed key issues of head lice, intestinal parasites, tuberculosis (TB), handwashing, and germ transmission. An interactive, multi-station health education session in the local language produced a significant increase in overall knowledge (mean score increased from 3.17 to 3.83 out of 5, p < 0.0001), with the largest increase among the adult group aged 31–50 years. This was most notable for handwashing knowledge, which had the greatest increase, and misconceptions about intestinal worms and head lice remained. Differences in outcome by age suggest the need for targeted educational strategies, particularly for teenagers and elderly individuals who achieved less gain. The results support the effectiveness of culturally tailored, community-based health education in promoting the awareness of disease among indigenous communities. The drawbacks are convenience sampling, the child dominance of the sample, and the short-term follow-up. Future emphasis should be placed on long-term, community-based intervention using culturally tailored content and digital media.